2019
DOI: 10.3390/jcm8010038
|View full text |Cite
|
Sign up to set email alerts
|

FAK is Required for Tumor Metastasis-Related Fluid Microenvironment in Triple-Negative Breast Cancer

Abstract: Cancer cell metastasis is the main cause of death in patients with cancer. Many studies have investigated the biochemical factors that affect metastasis; however, the role of physical factors such as fluid shear stress (FSS) in tumorigenesis and metastasis have been less investigated. Triple-negative breast cancer (TNBC) has a higher incidence of lymph node invasion and distant metastasis than other subtypes of breast cancer. In this study, we investigated the influence of FSS in regulating the malignant behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 58 publications
5
21
0
Order By: Relevance
“…2A, D and E). The data are in agreement with previous reports of FAK requirement to promote cell migration in MDA-MB-231 and MDA-MB-468 in breast cancer cell lines (35), and with the effect of FAK autophosphorylation at Y397 in cell migration, invasion, and proliferation of gastric carcinomas (36).
Figure 2Leptin-induced FAK activation occurs in a Src-dependent manner in MDA-MB-231 and MCF7 breast cancer cells.
…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2A, D and E). The data are in agreement with previous reports of FAK requirement to promote cell migration in MDA-MB-231 and MDA-MB-468 in breast cancer cell lines (35), and with the effect of FAK autophosphorylation at Y397 in cell migration, invasion, and proliferation of gastric carcinomas (36).
Figure 2Leptin-induced FAK activation occurs in a Src-dependent manner in MDA-MB-231 and MCF7 breast cancer cells.
…”
Section: Resultssupporting
confidence: 92%
“…6D and E). These data is consistent with the contribution of FAK to the highly invasive phenotype of the triple-negative MDA-MB-231 and BT549 cancer cells (35, 45).
Figure 7Leptin-induced secretion, activation of MMP-2 and MMP-9 and invasion in MDA-MB-231 cells is Src-dependent.
…”
Section: Resultssupporting
confidence: 88%
“…We observed differential expression of genes in these pathways and network analysis revealed key interactions that possibly contribute in EMT promotion and increased adhesiveness to endothelial cells during metastatic progression. These ndings support previous studies that reported modulation of cell signalling pathways involved in tumor metastasis in response to uid shear stress exposure in other cell types 25,56,59,66,67 . However, the signalling pathways and molecular mechanisms through which uid ow promotes EMT and adhesion of breast cancer cells to endothelial cells remain elusive and was not the focus of studies presented herein.…”
Section: Discussionsupporting
confidence: 91%
“…representing the most clinically aggressive subtype of breast cancer. This particular subtype is highly studied due to its unique biology, overall poor prognosis, early pattern for metastases and relative lack of therapeutic targets compared to the other subtypes 50,55,56 . Previous in vitro studies in which cancer cells were exposed to uid shear stresses in the range of those encountered in the tumor microenvironment have demonstrated promotion or induction of EMT 12,14,25,57,58,59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, we show that this effect is more pronounced in the basal MDA-MB-231 cells, representing the most clinically aggressive subtype of breast cancer. This subtype is highly studied due to its unique biology, overall poor prognosis, early pattern for metastases and relative lack of therapeutic targets compared to the other subtypes (51,(58)(59)(60). Previous in vitro studies in which cancer cells were exposed to uid shear stresses in the range of those encountered in the tumor microenvironment have demonstrated promotion or induction of EMT (12,24,(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%